‘Firsthand’ versus ‘Secondhand’ Perspectives of Harm Emphasising Teens’ Firsthand Perspectives of Online Sexual Content - See, Harrison; Woodley, Giselle (M/C - Media and Culture, 2024)
This article examines interview data from 24 Australian families, exploring how teens express perceived harms associated with online Sexually Explicit Material (SEM). For many teens, an encounter with SEM occurs prior to their first partnered sexual experience, often before their first kiss (Crabbe et al. 1; Power et al. 11; Woodley et al., Teen Perspectives 2). Of relevance was how teens expressed the potential harms of online SEM. Specifically, this article examines the difference between instances of teens expressing perceptions of SEM via the perspectives of others (secondhand perspectives) in contrast with instances of teens citing their own encounters with SEM (firsthand perspectives). Through thematic analysis, the authors argue that when making claims about teen experiences, firsthand perspectives should be emphasised where possible, given that secondhand perspectives often reflect media effects. Media effects refer to exacerbated fears in relation to the impact of media, often in the context that certain types of media are considered highly influential in shaping views and attitudes towards certain social and cultural phenomena (Tsaliki and Chronaki 402). As such, the authors aim to distinguish between teens' secondhand perceptions of potential harms – especially when observably informed by external influences – and their firsthand accounts of harm informed by their direct encounters with SEM. It is firsthand perspectives that the authors argue can lead to more effective policies. Further, the authors discuss how the use of loaded language during interviews can influence participant responses, particularly when collecting data on contentious or sensitive subjects such as SEM.